2022
DOI: 10.2217/bmm-2021-0536
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker Evaluation for Prognostic Stratification of Patients with Covid-19: the Added Value of Quantitative Chest Ct

Abstract: Aim: Pulmonary disease burden and biomarkers are possible predictors of outcomes in patients with COVID-19 and provide complementary information. In this study, the prognostic value of adding quantitative chest computed tomography (CT) to a multiple biomarker approach was evaluated among 148 hospitalized patients with confirmed COVID-19. Materials & methods: Patients admitted between March and July 2020 who were submitted to chest CT and biomarker measurement (troponin I, D-dimer and C-reactive protein) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Troponin values on admission could also perform as an indirect marker of non-cardiovascular damage during the disease's inflammatory cascade. Previous studies have demonstrated an association between higher troponin levels, greater total pulmonary opacification percentages, and lower lung volumes in hospitalized patients with COVID-19 11 . In the current study, those with hs-TnI elevation also presented with significantly greater lung involvement on computed tomography.…”
Section: Discussionmentioning
confidence: 95%
“…Troponin values on admission could also perform as an indirect marker of non-cardiovascular damage during the disease's inflammatory cascade. Previous studies have demonstrated an association between higher troponin levels, greater total pulmonary opacification percentages, and lower lung volumes in hospitalized patients with COVID-19 11 . In the current study, those with hs-TnI elevation also presented with significantly greater lung involvement on computed tomography.…”
Section: Discussionmentioning
confidence: 95%